A Rapid, Comprehensive Liquid Chromatography-Mass Spectrometry (LC-MS)-based Survey of the Asp Isomers in Crystallins from Human Cataract Lenses - Fujii, Norihiko (American Society for Biochemistry and Molecular Biology, 2012)
Cataracts are caused by clouding of the eye lens and may lead to partial or total loss of vision. The mechanism of cataract development, however, is not well understood. It is thought that abnormal aggregates of lens proteins form with age, causing loss of lens clarity and development of the cataract. Lens proteins are composed of soluble α-, β-, and γ-crystallins, and as long lived proteins, they undergo post-translational modifications including isomerization, deamidation, and oxidation, which induce insolubilization, aggregation, and loss of function that may lead to cataracts. Therefore, analysis of post-translational modifications of individual amino acid residues in proteins is important. However, detection of the optical isomers of amino acids formed in these proteins is difficult because optical resolution is only achieved using complex methodology. In this study, we describe a new method for the analysis of isomerization of individual Asp residues in proteins using LC-MS and the corresponding synthetic peptides containing the Asp isomers. This makes it possible to analyze isomers of Asp residues in proteins precisely and quickly. We demonstrate that Asp-58, -76, -84, and -151 of αA-crystallin and Asp-62 and -96 of αB-crystallin are highly converted to lβ-, dβ-, and dα-isomers. The amount of isomerization of Asp is greater in the insoluble fraction at all Asp sites in lens proteins, therefore indicating that isomerization of these Asp residues affects the higher order structure of the proteins and contributes to the increase in aggregation, insolubilization, and disruption of function of proteins in the lens, leading to the cataract.